Integrated nanoneedle-microfluidic system for single cell intracellular temperature measurement - Shaaban Binsilm, Salma Abdullah (2015)
Single cell analysis has become an important field of research in which cell properties are studied for an improved understanding of cellular processes. Cell intracellular temperature has proven to be a vital element in most cellular activates, chemical reactions and cell survival. An integrated nanothermal sensor-microfluidic system has been proposed to characterize the internal temperature of single cells. A finite element analysis study based on resistance temperature detectors has been studied. The first stage was to optimize the sensor design and dimensions where tungsten was chosen as a sensing material. Results show that a rectangular shape with a gap of 10.8 µm gave an equally distributed current density within the sensor, and 90 nm2 cross sectional area caused minimal damage to the cell. Further mechanical characterization has been done and the results show that the nanoneedle could resist ramp force applied before failure, up to 22.5 µN. The second stage was to test the nanoneedle ability to measure the temperature of a cell. Electrical measurement on yeast cell was done and the results show that the nanoneedle conductivity was independent of cell conductivity. The nanoneedle proved to be able to measure the temperature with a current difference of 50 nA and the resolution was 0.015 °C in the range of 24-60 °C. The nanoneedle detected temperature change of 0.02 °C in 10 ms. The third stage was to integrate the nanoneedle with the microfluidic system and to study water flow behaviour in the microfluidic channel. Results show that 63 µm2 microchannel cross sectional area was optimum and flow rate of 24.6 pl/min allowed successful cell penetration with minimal cell damage. The developed system can be a good candidate to be used in early disease diagnoses. Also, the system has the potential to measure electrical properties of cells and to be used for single cell drug delivery.